A Multi‐Functional Highly Efficient Upconversion Luminescent Film with an Array of Dielectric Microbeads Decorated with Metal Nanoparticles. (12th February 2020) - Ahn, In‐Hwan; Yeo, Seon Ju; Jung, Kinam; Kang, Gumin; Shin, Dong‐Hun; Jang, Ho Seong; Kim, Byunghoon; Nam, Minwoo; Kwon, Seok Joon; Ko, Doo‐Hyun
Abstract: Upconversion nanoparticles (UCNPs) have been integrated with photonic platforms to overcome the intrinsically low quantum efficiency limit of upconversion luminescence (UCL). However, platforms based on thin films lack transferability and flexibility, which hinders their broader and more practical application. A plasmonic structure is developed that works as a multi‐functional platform for flexible, transparent, and washable near‐infrared (NIR)‐to‐visible UCL films with ultra‐strong UCL intensity. The platform consists of dielectric microbeads decorated with plasmonic metal nanoparticles on an insulator/metal substrate. Distinct improvements in NIR confinement, visible light extraction, and boosted plasmonic effects for upconversion are observed. With weak NIR excitation, the UCL intensity is higher by three orders of magnitude relative to the reference platform. When the microbeads are organized in a square lattice array, the functionality of the platform can be expanded to wearable and washable UCL films. The platform can be transferred to transparent, flexible, and foldable films and still emit strong UCL with a wide viewing angle. Abstract : A multi‐functional platform is investigated for flexible, transparent, washable upcoversion luminescence films with ultra‐strong upcoversion luminescence intensity. The platform consists of dielectric microbeads decorated with plasmonic metal nanoparticles. This provides substantial benefits and promotes a wider range of practical applications for upcoversion nanoparticles in wearable near‐infrared‐to‐visible displays and attachable/detachable near‐infrared sensors.